Frontiers of Fundamental Physics Proceedings of the Sixth International Symposium "Frontiers of Fundamental and Computational Physics", Udine, Italy, 26-29 September 2004 - Sidharth, B. G.; Honsell, Furio; De Angelis, Alessandro (Springer Netherlands : Imprint: Springer, 2006)
The Sixth International Symposium "Frontiers of Fundamental and Computational Physics", Udine, Italy, 26-29 September 2004, aimed at providing a platform for a wide range of physicists to meet and share thoughts on the latest trends in various, mainly cross-disciplinary research areas. This includes the exploration of frontier lines in High Energy Physics, Theoretical Physics, Gravitation and Cosmology, Astrophysics, Condensed Matter Physics, Fluid Mechanics. Such frontier lines were unified by the use of computers as an, often primary, research instruments, or dealing with issues related to information theory. The book contains contributions by Nobel Laureates Leon N. Cooper (1972) and Gerard 't Hooft (1999), and concludes with two interesting chapters on new approaches to Physics Teaching. Audience Graduate students, lecturers and researches in Physics.